Bevacizumab for the treatment of metastatic colorectal cancer complicated by abdominal aortic aneurysm and mural thrombus: a case report - Li, Yujun; Wu, Tong; Saeed, Muhammad Muddasar; Cui, Xiaonan (Frontiers in Oncology, 2024)
Bevacizumab, a humanized monoclonal antibody targeting vascular endothelial growth factor (VEGF), was the first anti-angiogenic agent incorporated into metastatic colorectal cancer treatment strategies and demonstrated broad-spectrum anti-tumor efficacy. Commonly reported adverse events include hypertension, proteinuria, gastrointestinal perforation, bleeding, and thromboembolism. However, there are only a few reports on abdominal aortic aneurysms (AAA) as a complication of bevacizumab therapy. Given the high risk of fatal rupture with AAA, we present a case of bevacizumab-associated AAA to raise clinician awareness of this possible, rare, and serious adverse reaction.